Geology of the correas massif, south of sÃo paulo state - da Mata, Suelen Portughesi [UNESP]; Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Godoy, Antonio Misson [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
The Massif Correas is located in São Paulo state south region, in the Itaboa district, Ribeirão Branco municipality and is related to neoproterozoic granitogenic evolution of the Central Mantiqueira Province, inserted in the Ribeira Belt south-central portion and in the Apiaí Terrain northern part. It highlights in the geological literature due to its correlation with the occurrence of mineralized greisens in cassiterite and wolframite and that constitute the Bairro dos Correas polymetallic deposit. The body covers an area of a granite stock of approximately 5 km², elongated ellipsoidal in the ENE-WSW direction and intrusive in Água Clara Formation metavolcanicsedimentary rocks, belonging to the Açungui Supergroup and in Granitic Complex Três Córregos rocks. Granite rocks are represented by varieties of gray to pink, isotropic and porphytic rocks and distinct in three facies called porphyritic monozogranite biotite, biotite-muscovite sienogranite porphyrytic, mica-albita porphyry granite with topaz and pegmatitic phase.
Geologia do maciço correas, sul do estado de são paulo
Keywords: Correas Granite; Geophysics; Petrography